2017
DOI: 10.1002/jwmg.21333
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening links between waterfowl research and management

Abstract: Waterfowl monitoring, research, regulation, and adaptive planning are leading the way in supporting science-informed wildlife management. However, increasing societal demands on natural resources have created a greater need for adaptable and successful linkages between waterfowl science and management. We presented a special session at the 2016 North American Duck Symposium, Annapolis, Maryland, USA on the successes and challenges of linking research and management in waterfowl conservation, and we summarize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The Wisconsin Department of Natural Resources (WI DNR) periodically surveys the state's waterfowl hunters (i.e., duck and goose hunters) to assess their level of satisfaction with regulations, opportunities, and their hunting experiences as a means of heeding the call to incorporate hunter preferences into adaptive management (Roberts et al ). We mined the long‐term data set of these survey results to investigate the role of hunter behavior in explaining differences in satisfaction ratings of Wisconsin duck hunters with an eye on improving experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Wisconsin Department of Natural Resources (WI DNR) periodically surveys the state's waterfowl hunters (i.e., duck and goose hunters) to assess their level of satisfaction with regulations, opportunities, and their hunting experiences as a means of heeding the call to incorporate hunter preferences into adaptive management (Roberts et al ). We mined the long‐term data set of these survey results to investigate the role of hunter behavior in explaining differences in satisfaction ratings of Wisconsin duck hunters with an eye on improving experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Sharp et al (2014) found that in a large survey of the beliefs and attitudes of the Australian general public towards kangaroo management, that although commercial kangaroo harvesting enjoyed a high level of support from the general public there was concern about its animal welfare impacts. Although stakeholders consulted during the development of AHM included a wide range of representatives -federal, state, and provincial governments; academics; non-government organisations; and waterfowl-interested citizenry -it did not include representatives from animal protection groups (NAWMP Committee and others 2012; Roberts et al 2018), and it would be important that delegates from these groups are involved in any active adaptive management program developed for the management of kangaroos.…”
Section: Iterative Phasementioning
confidence: 99%
“…These have motivated agencies to undertake a double‐loop planning process (USFWS ) whereby objectives, model structures, and other adjustments are being considered for revision, given what has been learned from the initial iterative phase. Adaptive Harvest Management remains an example of linking research and management in a structured way (Roberts et al ) consistent with the earliest charge of the MBT (section 704) requiring that “due regard” be given to bird abundance and distribution before authorizing hunting seasons.…”
Section: Foundations For Waterfowl Managementmentioning
confidence: 99%